"Channel Lines": A Simple Surgical Technique to Aid in Achieving Patient-specific Ante-version During Implantation of Uncemented Acetabular Cups. Issue 4 (December 2018) - Raghavan, Roshan; Plakogiannis, Christos
Abstract : Accurate acetabular cup placement is a crucial step for a successful total hip replacement. Transverse acetabular ligament is an important and reliable landmark that helps in determining the version during the placement of acetabular cups. However, the visualization of transverse acetabular ligament may not be easy as the view may be blocked by the implants and the instruments. We have devised a simple technique to aid in achieving patient-specific ante-version during implantation of uncemented acetabular cups by using "channel lines."